Mediating and moderating effects of authoritative parenting styles on adolescent behavioral problems - Sun, Li; Li, Ao; Chen, Meng; Li, LuYao; Zhao, Yan; Zhu, AnQi; Hu, Peng (Frontiers in Psychology, 2024)
Introduction: This study aimed to analyze how authoritative parenting affects behavioral problems among primary, junior high, and secondary high school students. Today, parental educational anxiety and parent-child relationship conflicts are common in China and are resulting in a high incidence of child behavioral problems. High-quality family education is becoming increasingly important in China.This study sought to provide a reference for developing responsive family education services. Methods:A total of 10,441 parents in Hubei Province, including urban and rural areas, were evaluated using the Parents' Education Anxiety Questionnaire, Parental Authority Parenting Questionnaire, Parent-Child Relationship Scale, and Self-Made Behavior Problem Scale to determine the internal mechanisms of child behavioral problems in the family system. To make the sample more representative, this study collected data from primary and secondary schools representative of the southeast, northwest, and center of Hubei Province; further, the number of parents involved in each school was controlled at approximately 300 to ensure that the final sample had analytical value. Results: Educational anxiety directly affected children's behavioral problems and indirectly affected them through the conflicts between parent and child. This conflict partially mediated educational anxiety and child behavioral problems, and authoritative parenting played a significant regulatory role in this relationship.Discussion: Higher levels of educational anxiety among parents increased the likelihood of a depressed family environment. This can lead to deteriorating parent-child relationships, which can result in children's problem behaviors. Parents can address these problems by changing their approach to education and adjusting their emotions accordingly.